2016
DOI: 10.1242/dev.135392
|View full text |Cite
|
Sign up to set email alerts
|

Alk1 controls arterial endothelial cell migration in lumenized vessels

Abstract: Heterozygous loss of the arterial-specific TGFβ type I receptor, activin receptor-like kinase 1 (ALK1; ACVRL1), causes hereditary hemorrhagic telangiectasia (HHT). HHT is characterized by development of fragile, direct connections between arteries and veins, or arteriovenous malformations (AVMs). However, how decreased ALK1 signaling leads to AVMs is unknown. To understand the cellular mis-steps that cause AVMs, we assessed endothelial cell behavior in alk1-deficient zebrafish embryos, which develop cranial AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
98
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 45 publications
6
98
2
Order By: Relevance
“…As described above, arterial EC migration against the direction of blood flow is impaired in zebrafish acvrl1 mutants [183], and similar abnormal EC migratory behavior was recently described in Eng -deleted ECs in mice. In the latter model, Eng -deleted cells migrate aberrantly in the direction of flow and accumulate in arterioles, and enlarged arterioles ultimately become the afferent segments of AVMs [89].…”
Section: Cellular Mechanisms Of Avm Developmentmentioning
confidence: 74%
See 4 more Smart Citations
“…As described above, arterial EC migration against the direction of blood flow is impaired in zebrafish acvrl1 mutants [183], and similar abnormal EC migratory behavior was recently described in Eng -deleted ECs in mice. In the latter model, Eng -deleted cells migrate aberrantly in the direction of flow and accumulate in arterioles, and enlarged arterioles ultimately become the afferent segments of AVMs [89].…”
Section: Cellular Mechanisms Of Avm Developmentmentioning
confidence: 74%
“…In these mutants, AVMs invariably develop between 32 and 48 hours post-fertilization in cranial vessels that underlie the hindbrain; therefore, AVM development can be imaged in embryos expressing EC-localized fluorescent transgenes using time-lapse confocal microscopy [67, 68, 183]. These imaging studies have revealed that AVM development is a two-step process (Figure 3).…”
Section: Cellular Mechanisms Of Avm Developmentmentioning
confidence: 99%
See 3 more Smart Citations